2019
DOI: 10.1111/1346-8138.15073
|View full text |Cite
|
Sign up to set email alerts
|

Japanese real‐world study of sequential nivolumab and ipilimumab treament in melanoma

Abstract: To describe the treatment patterns of nivolumab and ipilimumab in Japan, a retrospective observational study was conducted in melanoma patients who received nivolumab and ipilimumab sequentially. Patients who received nivolumab and ipilimumab in combination were excluded from this study. Efficacy was evaluated by the Response Evaluation Criteria in Solid Tumors (RECIST) in terms of the overall response rate (ORR), progression‐free survival (PFS), and disease control rate (DCR). Overall survival (OS) was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Finally, 18 studies including 2054 patients were included in the meta-analysis. [27][28][29][30][31][38][39][40][41][42][43][44][45][46][47][48][49][50] The main characteristics of the included studies were summarized in Table 1. All the studies were published between 2015 and 2020, with 5 studies published before 2018.…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
“…Finally, 18 studies including 2054 patients were included in the meta-analysis. [27][28][29][30][31][38][39][40][41][42][43][44][45][46][47][48][49][50] The main characteristics of the included studies were summarized in Table 1. All the studies were published between 2015 and 2020, with 5 studies published before 2018.…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
“…Eventually selected were 13 studies [23,24,26–36] involving 2328 individuals and concerning NLR, and 42 articles [24–26,30–32,34,36–69] including 5907 patients with regard to LDH. Seven studies [24,26,30–32,34,36] reported both NLR and LDH associated with OS or PFS. As the study by Wagner et al [62] included 2 cohorts, in which patients were treated with different regimens and reported the HR and 95% CI, respectively, we termed them as “ Wagner 2018 cohort 1” and “ Wagner 2018 cohort 2.” The characteristics of the selected studies are summarized in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Country Agent Sample size NLR cutoff Survival analysis Analysis model NOS Ascierto 2019 [24] United States Nivolumab\Pembrolizumab 71 5 OS/PFS Multivariate 7 Bartlett 2020 [23] United States Pembrolizumab 224 5 OS Multivariate 7 Balatoni 2018 [27] Hungary Ipilimumab 47 4 OS Univariate 6 Capone2018 [28] Italy Nivolumab 97 5 OS/PFS Multivariate 7 Cassidy 2017 [29] United States Ipilimumab 197 5 OS/PFS Multivariate 8 Chasseuil 2018 [30] France Nivolumab 87 3 OS/PFS Multivariate 7 Ferrucci 2016 [31] Italy Ipilimumab 720 [35] United States Nivolumab plus Ipilimumab 209 4.73 OS Multivariate 7 Tsutsumida 2019 [26] Japan PD-1/PD-L1 + CTLA-4 68 4 OS Multivariate 7 Zaragoza 2016 [36] France Ipilimumab 58 4 OS Multivariate 7…”
Section: Studymentioning
confidence: 99%
“…Interestingly, the neutrophil to lymphocyte ratio appears to correlate with overall immune status and predicts the likelihood of response, with a high N/L ratio associated with a lower likelihood of benefit 23,24 . Other general markers of the immune state such as C‐reactive protein, a marker of inflammation, have demonstrated some value in assessing responsiveness 25 …”
Section: Predictors Of Response To Neoadjuvant Therapymentioning
confidence: 99%